A difference equation

Calculus Level 2

Given the sequence x n x_n , with x 0 = 0 x_0 = 0 , x 1 = 1 x_1 = 1 , and x n + 2 = 2 x n + 1 + 3 x n x_{n+2} = 2 x_{n+1} + 3 x_n for n 0 n \ge 0 . Find the following limit.

lim n x n + 1 x n \large \lim_{n \to \infty} \frac{ x_{n+1}}{x_n }


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 10, 2018

The linear recurrence relation x n + 2 = 2 x n + 1 + 3 x n x_{n+2} = 2x_{n+1} + 3x_n has the following characteristic equation.

r 2 = 2 r + 3 r 2 2 r 3 = 0 ( r 3 ) ( r + 1 ) = 0 x n = c 1 ( 3 n ) + c 2 ( 1 ) n Putting n = 0 x 0 = c 1 + c 2 = 0 c 2 = c 1 x 1 = 3 c 1 c 2 = 4 c 1 = 1 c 1 = 1 4 x n = 1 4 ( 3 n + ( 1 ) n + 1 ) \begin{aligned} r^2 & = 2r+3 \\ r^2 - 2r - 3 & = 0 \\ (r-3)(r+1) & = 0 \\ \implies x_n & = c_1(3^n) + c_2(-1)^n & \small \color{#3D99F6} \text{Putting }n=0 \\ x_0 & = c_1 + c_2 = 0 & \small \color{#3D99F6} \implies c_2 = -c_1 \\ x_1 & = 3c_1 - c_2 = 4c_1 = 1 & \small \color{#3D99F6} \implies c_1 = \frac 14 \\ \implies x_n & = \frac 14 \left(3^n + (-1)^{n+1}\right) \end{aligned}

Therefore,

L = lim n x n + 1 x n = lim n 3 n + 1 + ( 1 ) n 3 n + ( 1 ) n + 1 Divide up and down by 3 n . = lim n 3 + ( 1 ) n 3 n 1 + ( 1 ) n + 1 3 n = 3 \begin{aligned} L & = \lim_{n \to \infty} \frac {x_{n+1}}{x_n} \\ & = \lim_{n \to \infty} \frac {3^{n+1} + (-1)^n}{3^n + (-1)^{n+1}} & \small \color{#3D99F6} \text{Divide up and down by }3^n. \\ & = \lim_{n \to \infty} \frac {3 + \frac {(-1)^n}{3^n}}{1 + \frac {(-1)^{n+1}}{3^n}} \\ & = \boxed 3 \end{aligned}

Tom Engelsman
Sep 9, 2018

The above difference equation has the characteristic equation:

r 2 2 r 3 = ( r + 1 ) ( r 3 ) = 0 r = 1 , 3 r^2 - 2r - 3 = (r+1)(r-3) = 0 \Rightarrow r = -1,3

and the sequence x n = A ( 1 ) n + B ( 3 ) n x_{n} = A(-1)^n + B(3)^n . Using the initial conditions x 0 = 0 , x 1 = 1 x_{0}=0, x_{1}=1 , we obtain:

0 = A + B 0 = A + B and 1 = A + 3 B 1 = -A + 3B

or A = 1 4 , B = 1 4 A = -\frac{1}{4}, B = \frac{1}{4} so that our sequence is described by x n = 1 4 [ 3 n + ( 1 ) n + 1 ] x_n = \frac{1}{4} \cdot [3^n + (-1)^{n+1}] . For the above limit x n + 1 x n , n \frac{x_{n+1}}{x_{n}}, n \rightarrow \infty we have 1 4 [ 3 n + 1 + ( 1 ) n + 2 ] 1 4 [ 3 n + ( 1 ) n + 1 ] \frac{ \frac{1}{4} \cdot [3^{n+1} + (-1)^{n+2}] }{ \frac{1}{4} \cdot [3^n + (-1)^{n+1}] } . If we let u = 3 n , v = ( 1 ) n u = 3^n, v = (-1)^{n} , then we have:

3 u + v u v = 3 + 4 v u v = 3 + 4 ( 1 ) n 3 n + ( 1 ) n + 1 \frac{3u + v}{u-v} = 3 + \frac{4v}{u-v} = 3 + \frac{4(-1)^{n} }{3^n + (-1)^{n+1}}

As n n \rightarrow \infty , the quanitity 3 n + ( 1 ) n + 1 3^n + (-1)^{n+1} grows much faster than 4 ( 1 ) n 4(-1)^n (which is bounded to ± 4 \pm 4 ). The limit is ultimately equal to 3 + 0 = 3 . 3 + 0 = \boxed{3}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...